Analisis Nilai Pendidikan Karakter pada Tokoh Sejarah Lokal Sumatera Barat Sebagai Sumber Belajar dalam Pembelajaran Sejarah - Lionar, Uun; Fithriah, Rahmuliani (Jurnal Paedagogy, 2023)
This study aims to analyze and find the value of character education in Chatib Sulaiman and Bagindo Aziz Chan figures based on the main character indicators from the Ministry of Education and Culture, namely religious, nationalist, independent, mutual cooperation, and integrity. This study used a historical research methods consisting of: (1) heuristics, primary and secondary data searching and collection through literature review and interviews; (2) source criticism, carried out by analyzing, verifying, and testing the data that has been obtained; (3) interpretation, compiling data into a complete understanding; and (4) historiography, presenting research results in the form of research reports on the analysis of the value of character education in local historical figures of West Sumatra. The results of this study indicated that Chatib Sulaiman and Bagindo Aziz Chan attach religious, nationalist, independent, mutual cooperation, and integrity values which are represented through their life as figures in West Sumatra. The most prominent of these two figures is the nationalist character, both of whom died in the struggle to maintain the existence of the Republic of Indonesia.